PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR UTAMA DAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2016) - Nadya Shinta Savira Gunawan; Inten Meutia; Yusnaini Yusnaini (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2018)
The purpose of this research is to test whether there is influence of Corporate Social Responsibility disclosure and leverage on tax aggressiveness. The theories used in this research are Stakeholder Theory and Debt Covenant Hypothesis from Positive Accounting Theory. The type of this research is quantitative research. The population in this research is all main and manufacturing sector companies listed on the Indonesia Stock Exchange for the period 2014-2016. The total of companies selected as samples are 75 companies with the period research for three years, so the total of samples in this research are 225 samples that have been selected using purposive sampling technique. The data used in this study is secondary data in the form of annual reports of main and manufacturing sector companies listed on the Indonesia Stock Exchange for the period 2014-2016. Data collection technique used is documentation. The data analysis technique used is panel data regression. The results of this research showed that Corporate Social Responsibility disclosure has no influence on tax aggressiveness while leverage has negative and significant influence on tax aggressiveness.